Dysregulation of MicroRNA Regulatory Network in Lower Extremities Arterial Disease - Bogucka-Kocka, Anna; Zalewski, Daniel P.; Ruszel, Karol P.; Stępniewski, Andrzej; Gałkowski, Dariusz; Bogucki, Jacek; Komsta, Łukasz; Kołodziej, Przemysław; Zubilewicz, Tomasz; Feldo, Marcin; Kocki, Janusz (Frontiers in Genetics, 2019)
Atherosclerosis and it’s comorbidities are the major contributors to the global burden of death worldwide. Lower extremities arterial disease (LEAD) is a common manifestation of atherosclerotic disease of arteries of lower extremities. MicroRNAs belong to epigenetic factors that regulate gene expression and have not yet been extensively studied in LEAD. We aimed to indicate the most promising microRNA and gene expression signatures of lower extremities arterial disease, to identify interactions between microRNA and genes and to describe potential effect of modulated gene expression. High-throughput sequencing was employed to examine microRNAome and transcriptome of peripheral blood mononuclear cells of patients with LEAD, in relation to controls. Statistical significance of microRNAs and genes analysis results was evaluated using DESeq2 and Uninformative Variable Elimination by Partial Least Squares (UVE-PLS) methods. Altered expression of 26 microRNAs (hsa-let-7f-1-3p, hsa-miR-34a-5p, -122-5p, -3591-3p, -34a-3p, -1261, -21-5p, -15a-5p, -548d-5p, -34b-5p, -424-3p, -548aa, -548t-3p, -4423-3p, -196a-5p, -330-3p, -766-3p, -30e-3p, -125b-5p, -1301-3p, -3184-5p, -423-3p, -339-3p, -138-5p, -99a-3p and -6087) and 14 genes (AK5, CD248, CDS2, FAM129A, FBLN2, GGT1, NOG, NRCAM, PDE7A, RP11-545E17.3, SLC12A2, SLC16A10, SLC4A10 and ZSCAN18) were the most significantly differentially expressed in LEAD group compared to controls. Discriminative value of revealed microRNAs and genes were confirmed by Receiver Operating Characteristics (ROC) analysis. Dysregulations of 26 microRNAs and 14 genes were used to propose novel biomarkers of LEAD. Regulatory interactions between biomarker microRNAs and genes were studied in silico using R multiMiR package. Functional analysis of genes modulated by proposed biomarker microRNAs was performed using DAVID 6.8 tools and revealed terms closely related to atherosclerosis and, interestingly, the processes involving nervous system. The study provides new insight into microRNA-dependent regulatory mechanisms involved in pathology of LEAD. Proposed microRNA and gene biomarkers of LEAD may provide new diagnostic and therapeutic opportunities.